“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Promouvoir des programmes d'éducation à la sexualité positive, inclusive et émancipatrice: méta-analyse qualitative intersectionnelle des besoins exprimés par les jeunes - Descheneaux, Julie; Fédération du Québec pour le Planning des naissances; Pagé, Geneviève; Piazzesi, Chiara; Pirotte, Magaly (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; approches et analyses; discipline; intersectionnalité; pratiques féministes; pédagogie; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; santé sexuelle; thématiques; éducation

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques